2016
DOI: 10.1371/journal.pone.0166876
|View full text |Cite|
|
Sign up to set email alerts
|

iTRAQ-Based Quantitative Proteomic Analysis of Spirulina platensis in Response to Low Temperature Stress

Abstract: Low temperature (LT) is one of the most important abiotic stresses that can significantly reduce crop yield. To gain insight into how Spirulina responds to LT stress, comprehensive physiological and proteomic analyses were conducted in this study. Significant decreases in growth and pigment levels as well as excessive accumulation of compatible osmolytes were observed in response to LT stress. An isobaric tag for relative and absolute quantitation (iTRAQ)-based quantitative proteomics approach was used to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 70 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…A PsbO -deficient mutant of Arabidopsis had retarded development, pale leaves, and increased sensitivity to light stress [37]. The PsbO protein, however, is downregulated under LT stress in Spirulina , which causes a decreased electron transfer rate and photosynthetic capacity [38]. This supports that PsbO plays a dominant role in protecting and stabilizing the catalytic center as an important protein for Mn 4 Ca cluster stabilization [39].…”
Section: Discussionmentioning
confidence: 99%
“…A PsbO -deficient mutant of Arabidopsis had retarded development, pale leaves, and increased sensitivity to light stress [37]. The PsbO protein, however, is downregulated under LT stress in Spirulina , which causes a decreased electron transfer rate and photosynthetic capacity [38]. This supports that PsbO plays a dominant role in protecting and stabilizing the catalytic center as an important protein for Mn 4 Ca cluster stabilization [39].…”
Section: Discussionmentioning
confidence: 99%
“…NAD(P)H-quinone oxidoreductase and ATP synthase (delta and B chain) proteins were previously shown to be suppressed in maize under cold stress [ 63 ]. Cytochrome b6-f complex proteins were also suppressed in coconut and Spirulina in response to low-temperature stress [ 6 , 75 ]. Oxygen-evolving enhancer (OEE) protein is involved in cold acclimation in wheat crops [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies from recent years have demonstrated the successful use of iTRAQ-based global and phosphoproteomics quantitation in plants (Chen et al, 2016;Li et al, 2016;Nguyen et al, 2012;Wang, Hajano, Ren, Lu, & Wang, 2015). The use of iTRAQ and TMT multiplexing has proven useful in our comparative plant experiments.…”
Section: Background Informationmentioning
confidence: 99%